New refrigerants for air conditioning and refrigeration systems - Wylie, David (Fairmont Press ; Distributed by Prentice-Hall PTR, 1996)
Here is your complete answer book covering the new refrigerants and associated technologies currently being used to achieve CFC-related regulatory compliance in air conditioning and refrigeration systems. Emphasizing practical issues, the author covers impact of refrigerant replacement on chiller efficiencies, current technology options including upgrading versus replacement, refrigerant supply and demand considerations, and the best strategies for handling an EPA audit. In addition, guidelines are presented for establishing a refrigerant management program and for monitoring its effectiveness. Several case studies illustrate successfully implemented programs.